CT-01 Phase IB study of IMMU-115 (humanised ANTI-CD74 antibody) targeting antigen presenting cells in patients with systemic lupus erythematosus (SLE). (31st August 2016) - Wallace, Daniel J; Wegener, William A; Horne, Heather; Goldenberg, David M
Abstract : Background: IMMU-115 (milatuzumab), a humanised antibody targeting the CD74 antigen on antigen-presenting cells (APC), is being investigated in haematological malignancies. Since dysregulation of APCs may occur in autoimmunity, IMMU-115 could potentially help control disease activity in SLE. Following promising preclinical studies, IMMU-115 was reformulated for convenient administration by subcutaneous (SC) injection, and this initial study was undertaken. Materials and methods: Phase I, dose-escalation study in adults with SLE (ACR revised criteria) and positive ANA (titer ≥1:80), with moderate disease activity but not severe flares (at least 2 BILAG B's, but no A's) despite ≥5 mg/day prednisone. Background lupus medications continue with SC IMMU-115 administered weekly for 4 consecutive weeks. Disease activity is assessed by BILAG2004 and SELENA-SLEDAI every 4 weeks until week 24 Results: Ten patients (9F/1 M; median age, 37; median disease-duration, 7 years) have now completed dose level one, receiving 250 mg doses of IMMU-115 injected once-weekly for 4 weeks. They were on prednisone (5–20 mg/day, n = 10), antimalarials (n = 7), and immunosuppressives (n = 2) with mean SLEDAI 9.6 and BILAG-B activity in the musculoskeletal (n = 10), mucocutaneous (n = 9), cardiorespiratory (n = 1), and renal (n = 1) body systems. All patients improved in ≥1 body system, eliminating most musculoskeletal B's (9/10, 90%) and mucocutaneous B's (7/9, 78%) by week 8, with the single cardiorespiratory B eliminated by week 20, and the renal B vacillating between B and C over the study. Four patients flared post-treatment with new B-level disease at weeks 8, 12 and 20 (all cardiorespiratory) and week 24 (neuropsychiatric). Following treatment, mean total BILAG (scored using B = 5, C = 1, D/E = 0) decreased 43% and mean SLEDAI decreased 54%, both measures remaining decreased through week 24 (Figure 1 ). Adverse events were Grade 1–2 (mild-moderate) and predominantly injection site (n = 7) or constitutional/flu-like (n = 9) reactions managed with supportive medication (steroids, antihistamines, anti-pyretics). Routine safety and other laboratories (B/T cells, monocytes, dendritic cells, serum immunoglobulins, cytokines, ANA, other autoantibodies, CRP, C3) were unremarkable. One patient developed anti-IMMU-115 antibodies of uncertain clinical significance, resolving within 3 months. Conclusions: IMMU-115 showed evidence of therapeutic efficacy with acceptable toxicity already at the first dose level, including suppression of disease activity extending 24 weeks in most patients. To confirm these results, further dose escalation was suspended with patients currently being randomised under double-blind conditions to receive treatment with 250 mg doses, a reduced dose of 100 mg, or placebo control. Acknowledgements: Supported in part by U.S. Department of Defense Grant W81XWH-13–1-0392. Trial Registration: Clinicaltrials.gov identifier: NCT01845740